Enhancing the Economics and Environmental Sustainability of the Manufacturing Process for Air-Blown bitumen. (10th November 2021) - Hajikarimi, Pouria; Shariati, Saba; Rahi, Mohammad; Kazemi, Ruhollah; Nejad, Fereidoon Moghadas; Fini, Elham H.
Abstract: This study exploits silica and polyphosphoric acid (PPA) synergistic effects to produce air-blown bitumen with desired stiffness and reduced carbon footprint. This in turn enhances the durability of the resulting air-blown bitumen while reducing gaseous emissions associated with its production. Here, we hypothesize that PPA-grafted silica made by adsorption of polyphosphoric acid to pristine silica nanoparticles promotes intermolecular interactions in vacuum bottom (VB), facilitating the production of air-blown bitumen. To test this hypothesis, laboratory experiments and modeling were used to determine the underlying molecular interactions determining PPA-grafted silica's role in facilitating the production of air-blown bitumen. Our molecular modeling showed PPA promotes the interaction between VB molecules by up to 10.28%; this combined with the increased polarity of VB molecules during the air-blowing process, leads to a significant increase in intermolecular interactions accelerating VB's stiffening. The latter was evidenced in our experiments showing that the required air-blowing time to reach desired stiffness measured by penetration and softening point was reduced up to 25% (time to reach required stiffness was reduced from 120 min to 90 min when silica-grafted polyphosphoric acid was used). Reduction of manufacturing time reduces VB's exposure to heat which leads to the formation of secondary organic aerosols. This promotes the economic and environmental sustainability aspects of the air-blowing process and contributes to resource conservation. Graphical abstract: Image 1